Metabolic gene therapy in a canine with pulmonary hypertension secondary to degenerative mitral valve disease - Katz, Michael G.; Ohad, Dan G.; Putter, Philip; Shtraizent, Nataly; Shahar, Ehud; Tal, Smadar; Eliyahu, Efrat (Frontiers in Veterinary Science, 2024)
Myxomatous mitral valve disease (MMVD) stands out as the most prevalent acquired canine heart disease. Its occurrence can reach up to 40% in small breed dogs and escalates in geriatric canine populations. MMVD leads to thickening and incomplete coaptation of valve leaflets during systole, resulting in secondary mitral valve regurgitation. Serious complications may arise concurrently with the worsening of mitral valve regurgitation, including left-and right-sided congestive heart failure, and pulmonary hypertension (PH). Ultimately, the PH progression might contribute to the patient’s demise or to the owner’s decision of euthanasia. Most currently available FDA-approved therapies for PH are costly and aim to address the imbalance between vasoconstriction and vasodilation to restore endothelial cell function. However, none of these medications impact the molecular dysfunction of cells or impede the advancement of pulmonary vascular and right ventricular remodeling. Recent evidence has showcased successful gene therapy approaches in laboratory animal models of PH. In this manuscript, we summarize the latest advancements in gene therapy for the treatment of PH in animals. The manuscript incorporates original data showcasing sample presentations, along with non-invasive hemodynamic assessments. Our findings demonstrate that the use of metabolic gene therapy, combining synthetic adeno-associated virus with acid ceramidase, has the potential to significantly reduce the need for drug treatment and improve spontaneously occurring PH in dogs.